Satisfactionâs Level of Hypertensive Patients towards Pharmacy Counseling with Al-Quran Based at Karya Sehat Pharmacy in Purwokerto, Banyumas Regency - Galistiani, Githa F.; Wibowo, Much I. N. A.; Gladiawati, Rachmi; Merishandy, Dwi (Indonesian Journal of Clinical Pharmacy, 2018)
Hypertension is a major cause of death in some countries. World Health Organization (WHO) estimated there are 11% of undetected hypertension in which 50% of them are living in developing countries such as Indonesia, with the incidence of 25.8%. Pharmaceutical counseling is one of the most comprehensive pharmacist services. Therefore, pharmacistsâ participation through counseling is needed to provide pharmacological therapy by administration of antihypertensive medication and nonpharmacological therapy, for instance by recital of Al-Quran during pharmaceutical therapy which become the objective of this study. This research aimed to determine satisfactionâs level of hypertensive patients with the intervention of pharmaceutical counseling with Al-Quran based as well as effectiveness of the therapy. This research was conducted from February until March 2017 at Karya Sehat Pharmacy in Banyumas regency. This research is an experimental with post test only design group methods. Data in this study is quantitative data with questionnaires as research instruments. Result of this research showed that the satisfactionâs level of patients with usual care counseling and Al-Quran based pharmacy counseling had CSI values of 73.55% and 72.63%, respectively. There is no difference of level of satisfaction between the two groups. Both of pharmacy counseling methods can be applied in pharmacy services to improve patientsâs satisfaction.Keywords: Hypertension, patientâs satisfaction, pharmaceutical counselingÂ Tingkat Kepuasan Pasien dalam Pelayanan Konseling Kefarmasian Berbasis Al-Quran di Apotek Karya Sehat Purwokerto, Kabupaten BanyumasHipertensi menjadi penyebab utama kematian di beberapa negara. World Health Organization (WHO) memperkirakan terdapat 11% pasien hipertensi di dunia yang tidak terdeteksi dan 50% di antaranya berada di negara berkembang, salah satunya di Indonesia dengan angka kejadian sebesar 25,8%. Konseling kefarmasian merupakan salah satu pelayanan apoteker yang komprehensif. Untuk itu, diperlukan partisipasi aktif apoteker melalui konseling di apotek yang mudah ditemui oleh masyarakat untuk memberikan terapi farmakologi berupa pemberian obat antihipertensi dan penyaranan terapi nonfarmakologi, salah satunya berupa penganjuran membaca Al-Quran pada saat melakukan konseling kefarmasian. Penelitian ini bertujuan untuk mengetahui tingkat kepuasan pasien hipertensi yang mendapatkan intervensi konseling kefarmasian berbasis Al-Quran terhadap pelayanan apoteker serta efektivitas pengobatan pasien. Penelitian ini dilaksanakan pada bulan FebruariâMaret 2017 di Apotek Karya Sehat Purwokerto, Kabupaten Banyumas. Metode penelitian ini menggunakan eksperimental dengan pendekatan post test only groups design. Jenis data yang digunakan merupakan data kuantitatif dengan bantuan kuesioner sebagai instrumen penelitian. Tingkat kepuasan pasien yang mendapatkan konseling kefarmasian usual care dan konseling kefarmasian berbasis Al-Quran masing-masing memiliki nilai CSI sebesar 73.55% dan 72.63%. Tidak terdapat perbedaan tingkat kepuasan antara kedua kelompok. Kedua metode konseling kefarmasian dapat diterapkan dalam pelayanan kefarmasain untuk meningkatkan kepuasan pasien.Kata kunci: Hipertensi, kepuasan pasien, konseling kefarmasianÂ